Two-tier labor markets in the great recession: France vs Spain - Bentolila, Samuel; Cahuc, Pierre; Dolado, Juan José; Le Barbanchon, Thomas (Bonn, 2010)
"This paper analyzes the strikingly different response of unemployment to the Great Recession in France and Spain. Their labor market institutions are similar and their unemployment rates just before the crisis were both around 8%. Yet, in France, unemployment rate has increased by 2 percentage points, whereas in Spain it has shot up to 19% by the end of 2009. We assess what part of this differential is due to the larger gap between the dismissal costs of permanent and temporary contracts and the less restrictive rules regarding the use of the latter contracts in Spain. Using a calibrated search and matching model, we estimate that about 45% of the surge in Spanish unemployment could have been avoided had Spain adopted French employment protection legislation before the crisis started."